Civic Identity Formation through Digital Citizenship Learning in Higher Education - Hafidh Maksum; Halik Halik; Badratun Nafis; Maulidar Maulidar; Juanda Juanda (Jurnal Sosial, Politik dan Budaya (SOSPOLBUD), 2026)
This study assessed a Virginia tobacco (Nicotiana tabacum L.) bark–based botanical insecticide for controlling whitefly (Bemisia tabaci) and improving potato (Solanum tuberosum L.) yield. Using a completely randomized design with six concentrations (0–10%), results showed a significant negative linear relationship between insecticide concentration and pest population (R² = 0.98) and infestation intensity (R² = 0.99). The 10% concentration reduced pest populations by 22.82% and produced the lowest infestation levels. Pest population strongly correlated with infestation intensity (R² = 0.98). Yield increased markedly at 10%, with tuber number and weight rising by 66.67% and 82.93%, respectively (R² > 0.99). The insecticidal effect is attributed to nicotine alkaloids and toxic secondary metabolites. These findings highlight the potential of tobacco-based botanical insecticides as a sustainable component of integrated pest management.